Valproic acid intoxication – The importance of toxicological analysis and correct management: A case report - André Valle de Bairros; Karol Andriely de Vargas Paier; Leonardo Corrêa Cardoso; Fernanda Ziegler Reginato; Gustavo Andrade Ugalde; Ivy Bauer Lovatel; Miguel Roehrs (Toxicology Reports)
Introduction: Valproic acid (VPA) is an anticonvulsant widely used in treating epilepsy which can occur cases of poisoning in overdose situations. Case description: A 15-year-old girl purposely ingested about 100 drug tablets according to family members. Gastric lavage with activated charcoal was performed at home using a nasogastric tube and patient just was taken to the hospital around 10 h after drug ingestion, arriving in shock state. All laboratorial parameters were altered together a suspect of aspiration pneumonia with the presence of gross perihilar infiltrated in the right lung. Immunoassay screening test did not detect any substance; LC-UV detected quetiapine (> 150 ng/mL) while GC-MS determined 977.96 µg/mL of valproic acid in the patient’s plasma, confirming valproic acid intoxication. Appropriate life support was performed in the patient during hospitalization; however, she died two days later, reaching her suicide. Conclusions: Prognosis could be favorable if the patient was taken immediately to hospital emergency, considering the complexity of managing poisoning. Patient´s anamnesis must be carefully analyzed by the healthcare professional to avoid false conclusions and toxicological analysis is extremely important to clarify suspected poisoning.